Teachers’ Expressions in EFL Classrom at a Senior High School - Humaeroah, Humaeroah (Universitas Negeri Makassar, 2017)
Expression is one of the way people communicate with others deals with exploring feeling, meaning, idea, and suggestion by using verbal or non-verbal communication. The objectives of the research are to find out (1) types of Expressions uttered by teachers, (2) the dominant expressions uttered by teachers, and (3) the students’ responses toward teachers’ expressions. This research employed descriptive quantitative research design. This research took two English teachers and two classes of students in SMA Neg 11 Pinrang as the participants of the research which were taken through purposive sampling. The data of this research were collected by classroom observation, video recording and interview. The research findings show that (1) there are eight expression which uttered by teachers based on Alfaro’s classifications, they are greetings/farewells, spontaneous reaction, getting student’s attention, telling students to do something, encouraging expressions, organizing contents, time, and places, showing sympathy, checking students’ understanding, (2) telling student’s to do something is the mostly expressions uttered by teachers, (3) the students responses toward teachers’ expressions categorized into into two kinds, they are positive and negative response. Most of students gave positive responses on greetings, spontaneous reaction and encouraging expressions by giving feedback, doing teacher’s instruction and feeling happy if the teachers uttered those expressions. Some of the students gave negative responses on the other expressions uttered by the teachers by ignoring their teacher expressions.. Key Words: Teachers’ expressions, expressions of Alfaro’s classifications, students’ response.